2018
DOI: 10.1515/eras-2018-0010
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Deviant Behaviour Among Public Sector Employees: The Roles of Perceived Religiosity and Job Status

Abstract: Workplace deviant behavior has been linked to a number of organizational losses such as decreased employee morale, increased turnover and loss of legitimacy among important external stakeholders. Therefore, this paper investigated the relationships between religiosity, job status and workplace deviant behavior. Participants consisted of 351 (F=178; Mean age=39.2) employees of the Local Government Service Commission in Nigeria. Data which were sourced through the Workplace Deviant Behavior Scale and Centrality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…desire for revenge) as compared to those who are low on religiosity. Previously Akanni et al (2018) have argued that religiosity reduces the risk of deviance and helps in creating positivity at work. Similarly, Murtaza et al (2020) found that religious beliefs moderate the effects of workplace incivility.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…desire for revenge) as compared to those who are low on religiosity. Previously Akanni et al (2018) have argued that religiosity reduces the risk of deviance and helps in creating positivity at work. Similarly, Murtaza et al (2020) found that religious beliefs moderate the effects of workplace incivility.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Akanni, Omisile and Oduaran [2] examined WDB among public sector employees: The roles of perceived religiosity and job status. Three hundred and fifty one (351) Nigerian workers of the Local Government Service Commission participated in the study.…”
Section: Empirical Review On Determinants Of Workplace Deviant Behavi...mentioning
confidence: 99%
“…However, the destructive perspective perceives negative consequences caused by these behaviours and thus, prescribes these destructive behaviours at the workplace to mean WDB [1]. Robinson and Bennett [2] labeled WDB as those acts of staff at the workplace that are not in conformity with the norms and rules of the organization and, as such, cause harm to the staff, clients or customers within the organization. The impact of WDB on the organization and its human elements cannot be undermined.…”
Section: Introductionmentioning
confidence: 99%
“…Although the topic of WD is not new (Robinson & Bennett, 1995), the factors contributing to this type of conduct constantly evolve as time and circumstances change (Baharom et al, 2017;Miraglia & Johns, 2021). According to Akanni et al (2019), public and private organisations worldwide deal with WD Otherwise known in different terminology (Adeoti et al, 2021) Workplace Deviance can be defined as behaviour that goes against established policies and procedures and threatens the organisation's success and the interests of its stakeholders (Marasi et al, 2018). It is categorised into organisational and interpersonal deviances.…”
Section: Introductionmentioning
confidence: 99%